Integrating teaching, learning, and action research : enhancing instruction in the K-12 classroom - Stringer, Ernest T. (Sage, 2010)
'Integrating Teaching, Learning, and Action Research: Enhancing Instruction in the K-12 Classroom' demonstrates how teachers can use action research as an integral component of teaching and learning. The text uses examples and lesson plans to demonstrate how student research processes can be incorporated into classroom lessons that are linked to standards.